Safety and efficacy of oral cancer vaccine B440 in patients with PD-1/PD-L1 inhibitor-resistant advanced urothelial cancer: a study protocol for a phase 1 multicenter, open-label, single-arm clinical trial - Junya Furukawa; Yasumasa Kakei; Sae Murakami; Hiroshi Kita; Hideto Ueki; Takuto Hara; Jun Teishima; Nobuyuki Hinata; Hideaki Miyake; Masato Fujisawa; Toshiro Shirakawa (BMC Cancer)
Abstract Background This is a multicenter, open-label, single-arm clinical trial to evaluate the safety and efficacy of oral cancer vaccine B440 in patients with PD-1/PD-L1 inhibitor-resistant advanced urothelial cancer. Methods The trial will be performed at three university hospitals in Japan. The target number of patients will be 12. The patients will be treated orally with B440 once daily for 5 days followed by 2 days for four consecutive courses (4 weeks, 20 treatments). The low-dose group will receive 800 mg (4 capsules) per dose and the high-dose group will receive 1,600 mg (8 capsules) per dose. The primary outcome will be the number and incidence of DLT cases the start of treatment and Day 28. Secondary outcomes are the presence or absence of a response, the best overall response and PFS. Discussion If this trial shows B440 to be safe and effective, it may lead to a late phase randomized controlled trial in advanced urothelial cancer. Ultimately, we hope to provide a new treatment option for such patients. Trial registration Japan Registry of Clinical Trials (jRCT) identifier: jRCT2051220143. Registered on December 27, 2022.